Diastereoselective synthesis of fused oxazolidines and highly substituted 1H-pyrrolo [2, 1-c][1, 4] oxazines via C–H functionalization1. Issue 76 (19th August 2015) - Pavan Kumar, Chottanahalli. S.; Harsha, Kachigere. B.; Mantelingu, Kempegowda; Rangappa, Kanchugarakoppal. S.
<x xml:space="preserve">Abstract</x> The first one pot protocol for the diastereoselective synthesis of oxazolo[2, 3-c]isoquinoline was achieved by metal-free, benzoic acid catalyzed reactions under mild conditions via C–H, C–O bond functionalization.